Implementing the WHO rehabilitation competency framework in undergraduate medical education: a context-specific adaptation for neurorehabilitation training - Zhou, Siyu; Zhang, Yuanmingfei; Yang, Yanyan; Liu, Jingyu; Qi, Wenjing (Frontiers in Neurology, 2025)
BackgroundThe World Health Organization (WHO) released the Rehabilitation Competency Framework (RCF) in 2020, encompassing five core domains—Practice, Professionalism, Learning and Development, Management and Leadership, and Research—along with cross-cutting values and beliefs that establish international standards for rehabilitation education. However, current neurorehabilitation training in Chinese clinical undergraduate programs lacks a competency-oriented structure. For example, Peking University’s existing curriculum includes only 8 lecture h and an optional 2-week practicum, with assessment predominantly based on written examinations rather than competency evaluation.MethodsCurriculum Design: We employed a Delphi method (involving 3 rounds with 13 experts) to construct an RCF-based curriculum system, defining entry-level proficiency competencies (e.g., Practice P1-P4 and Core Values V1-V4). Implementation: We delivered an 8-h RCF theory plus 2-h case-based learning (CBL) to 36 eight-year program undergraduates. We conducted paired t-tests to evaluate competency changes before and after the intervention. The Rehabilitation Physician Competence Questionnaire was used as the core assessment tool. Paired t-tests were conducted to compare the 13 competence indicators before and after the curriculum reform to verify the effectiveness of the competence-oriented teaching method.ResultsCurriculum Framework: Four modules—Professionalism, Foundations, Core Competencies, and Intensive Practicum—covering all RCF domains were developed. The Core Competencies module emphasized “Assessment Skills (P3)” and “Evidence-Based Decision Making (R1).” Outcomes: A total of 13 of 15 competencies showed significant improvement post-intervention (p < 0.05), including technical skills (+1.25 points) and empathy (+0.42 points). Research competency and patient advocacy showed non-significant changes.ConclusionThis study established a closed-loop system of “contextualized competency framework → curriculum development → multidimensional evaluation,” demonstrating RCF’s effectiveness in enhancing undergraduate rehabilitation competencies. It provides a paradigm for rehabilitation education aligned with Chinese characteristics.